THE IMPACT OF WORK DISCIPLINE, K3 AWARENESS, AND INCENTIVES ON EMPLOYEE PRODUCTIVITY - Andita, Vina; Eman Sulaiman; Elfira Destiyanti (Journal Of Resource Management, Economics And Business, 2025)
Purpose: This research aims to analyze work discipline, K3 awareness, incentives that influence employee work productivity at PT. Bhakti Sari Perkasa with Cirebon Branch. Descriptive analysis was carried out by collecting data from 78 employees through a questionnaire instrument. Research Methodology: The research results show that work discipline does not partially affect employee work productivity. Awareness of occupational safety and health partially influences employee work productivity by 76.3%. Incentives partially influence employee work productivity by 63.3%. Work discipline, awareness of occupational safety and health, and incentives simultaneously have a significant influence on employee work productivity of 87.5%. Results: These findings indicate the importance of maintaining work discipline, increasing K3 awareness, and providing appropriate incentives to increase employee work productivity. Contribution: Research recommendations include increasing awareness of work discipline, strengthening occupational safety and health programs, implementing an effective incentive system, as well as further research to understand other factors that can influence employee work productivity.